Efficiency of Trichoderma harzianum (strain A-34) and its culture filtrates on control of three rice fungal aerial diseases (Bioagro, 2020)
Due to the results obtained with the action mechanisms of competition, micoparasitism and antibiosis of Trichoderma harzianum Rifai (strainA -34), as well as the activity that its culture filtrates have demonstrated of on the causal agents of the diseases known as  brown spot (Bipolaris oryzae), sheath rot (Sarocladium oryzae) and rice blast (Pyricularia grisea), the objective of this study was to evaluate under semicontroled conditions the efficiency of the antagonist and its culture filtrates as alternative of control of those rice fungal aerial diseases. The investigation was conducted in the crop house of the Institute of Biotechnology of the Plants (IBP), belonging to the Central University "Marta Abreu" of Las Villas in the county of Villa Clara, Cuba, in the period of May to September 2012. The following nine treatments were studied: three concentrations of biological control agents, four dilutions of culture filtrates, one relative control (Azoxistrobina) and one absolute control. It was determined the control efficiency along with the epifhytologic variable of area under the disease progress curve (AUDPC). The rice variety used was Perla de Cuba.  The experiments showed that the antagonist and their culture filtrates controlled the fungal diseases with levels of efficiency between 70 and 90 %; also, a decrease superior to 67.5 % of AUDPC was obtained with the application of the biological control alternatives.
Keywords: Antagonist; Bipolaris oryzae; Sarocladium oryzae; Oriza sativa; Pyricularia grisea